Enhanced photodynamic leishmanicidal activity of hydrophobic zinc phthalocyanine within archaeolipids containing liposomes - Perez AP (Dove Medical Press, 2014)
Ana Paula Perez,1 Agustina Casasco,2 Priscila Schilrreff,1 Maria Victoria Defain Tesoriero,1,3 Luc Duempelmann,1 Maria Julia Altube,1 Leticia Higa,1 Maria Jose Morilla,1 Patricia Petray,2 Eder L Romero11Programa de Nanomedicinas, Departamento de Ciencia y Tecnología, Universidad Nacional de Quilmes, 2Servicio de Parasitología y Enfermedad de Chagas, Hospital de Niños Ricardo Gutiérrez, 3Unidad Operativa Sistemas de Liberación Controlada, Centro de Investigación y Desarrollo en Química, Instituto Nacional de Tecnología Industrial (INTI), Buenos Aires, ArgentinaAbstract: In this work, the in vitro anti-Leishmania activity of photodynamic liposomes made of soybean phosphatidylcholine, sodium cholate, total polar archaeolipids (TPAs) extracted from the hyperhalophile archaea Halorubrum tebenquichense and the photosensitizer zinc phthalocyanine (ZnPcAL) was compared to that of ultradeformable photodynamic liposomes lacking TPAs (ZnPcUDLs). We found that while ZnPcUDLs and ZnPcALs (130 nm mean diameter and –35 mV zeta potential) were innocuous against promastigotes, a low concentration (0.01 µM ZnPc and 7.6 µM phospholipids) of ZnPcALs irradiated at a very low-energy density (0.2 J/cm2) eliminated L. braziliensis amastigotes from J774 macrophages, without reducing the viability of the host cells. In such conditions, ZnPcALs were harmless for J774 macrophages, HaCaT keratinocytes, and bone marrow-derived dendritic cells. Therefore, topical photodynamic treatment would not likely affect skin-associated lymphoid tissue. ZnPcALs were extensively captured by macrophages, but ZnPcUDLs were not, leading to 2.5-fold increased intracellular delivery of ZnPc than with ZnPcUDLs. Despite mediating low levels of reactive oxygen species, the higher delivery of ZnPc and the multiple (caveolin- and clathrin-dependent plus phagocytic) intracellular pathway followed by ZnPc would have been the reason for the higher antiamastigote activity of ZnPcALs. The leishmanicidal activity of photodynamic liposomal ZnPc was improved by TPA-containing liposomes.Keywords: macrophages, Leishmania amastigotes, Zn intracellular delivery, irradiation